MOTIVASI BELAJAR MENURUT PERSPEKTIF AL-QUR’AN - Zaky, Muhammad; Deliani, Nurfarida; Batubara, Juliana (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
This study aims to examine the concept of learning motivation in the perspective of the Qur'an. The Qur'an as a source of Islamic teachings provides comprehensive guidance on the importance of seeking knowledge. Through various verses, the Qur'an inspires individuals to have strong learning motivation. This study uses a literature review method which allows a researcher to identify a theory or method, develop a theory or method, identify gaps that occur between a theory and relevance in the field/to a research result. In the field of education, there is no doubt that the existence of the Qur'an has influenced the education system. By studying the Qur'an, it can provide inspiration and motivation in aspects of life. By understanding the messages of the Quran about learning motivation, students can explore spiritual wisdom and apply it in their journey to learn and understand the universe.